Analysis of Tiger Shrimp (Panaeus monodon) Agribusiness System in Pinrang Regency (Agrikan Jurnal Agribisnis Perikanan, 2024)
Tiger shrimp is the main choice to be cultivated by farmers with simple technology. The research objectives are : (1) To describe the procurement and use of production facilities ; (2) Analyzing the business performance of tiger shrimp; (3) Describe the post-harvest process and processing of tiger shrimp business products; (4) Analyzing the marketing subsystem ; (5) Describe the support services. This research was carried out for 6 months (July 2021 to January 2022) in Pinrang Regency. Determination of research samples for farmers using the Simple Random Sampling method with 100 people respondents. Determination of stakeholders respondents using the snowball sampling method. The results showed; (1) Procurement and use of production facilities for tiger shrimp agribusiness system is running well because it is quite easy to obtain and in accordance with cultivation technology. (2) The performance of tiger shrimp farming is profitable which can be seen in terms of the average income for an area of 1.487 hectares of 13,076,189 IDR or 8.856,885 IDR/ hectares. The R/C-Ratio value of 2.25 (feasible to cultivate). (3) The postharvest process and processing of tiger shrimp farming include; pick-up of shrimp in ponds, spraying, sorting and grading, and packaging. The age of the first harvest is 60 days after stocking with a partial system. Next harvest 2 times a month for each pair (bonang); (4) The tiger shrimp marketing subsystem have efficient because the value of marketing efficiency is 14.11% and 33.33% ; (5) support services using transportation, agricultural extension, and government policies.
Keywords: Tiger Shrimp; Agribusiness System; Production Facilities; Farm Performance; Marketing Support System